A DFIG low- and High-Voltage cascading failure through strategy based on GSC and RSC joint control - Xu Zhang; Xin Xu; Yi Wang; Juan Wei (International Journal of Electrical Power & Energy Systems)
In wind power DC transmission systems, commutation failures cause significant reactive power fluctuations at the direct current (DC) transmission end, leading to sequential changes in voltage from low to high and often causing wind turbines to disconnect during low- to high-voltage cascading faults. Existing doubly fed induction generator (DFIG) control strategies typically involve decoupled control of the rotor-side converter (RSC) and grid-side converter (GSC) by overlooking the interactions between the stator and rotor during voltage ride-through and by limiting the transient response capability of wind turbines. Therefore, a DFIG low- to high-voltage cascading fault ride-through strategy based on the joint control of the GSC and RSC is proposed. First, the transient characteristics of a DFIG under low- to high-voltage cascading faults are analyzed to examine the influence of the stator current on the rotor voltage and the influence of the rotor current on the stator voltage. Accordingly, stator current deviation is introduced into the RSC voltage reference to enhance the transient reactive response of the DFIG, and rotor current deviation is introduced into the GSC voltage reference to stabilize the DC bus voltage to achieve coordinated control of the rotor- and grid-side converters. To maximize the joint control effect, different components of the stator flux linkage and PI components of the terminal voltage deviation are incorporated into the current references of the RSC and GSC to expand the reactive current boundary during fault ride-through and enable better reactive support by the DFIG during low- to high-voltage faults. Finally, the effectiveness of the proposed strategy under various complex conditions is verified on the MATLAB/Simulink platform.